Cancer Incidence and Distribution at a Tertiary Care Hospital in Somalia from 2017 to 2020: An Initial Report of 1306 Cases - Tahtabasi, Mehmet (Cancer Manag Res, 2020)
PURPOSE: To determine the type, frequency and distribution of all cancers in Somalia from 2017 to 2020. PATIENTS AND METHODS: This retrospective and descriptive study included the review of a total of 5238 pathology reports obtained from the medical records of the Somalia Turkey Recep Tayyip Erdogan Education and Research Hospital. Patient characteristics, lesion localization, and histopathology were recorded. Patients with an unconfirmed cancer diagnosis, borderline tumors, intraepithelial neoplasms and metastatic cancers were excluded from the study. The cases were classified according to gender, age, and organ involvement. RESULTS: Of the 1306 patients included in the study, 50.9% (n=666) were female and 49.1% (n=640) were male, and the mean age was 51.1±19.4 years. Of the cases, 5.1% (n=67) were pediatric (0–17 years) and 35.8% (n=468) were in the 18–50 years range. The most common cancer was esophageal cancer (EC) for the overall data (n=284; 21.7%) and in both genders. EC peaked in the fifth decade, and the most common histological type was squamous cell carcinoma (n=256; 91.1%). Liver cancer was the second most common cancer overall (n=99; 7.6%) and in men (n=67; 10.5%). Cervical cancer was the second most common cancer among women (n=88; 13.3%) and ranked fourth in terms of overall incidence (n=88; 6.7%). Breast cancer was the third most common overall (n=95; 7.3%) and in women (n= 87; 13.1%). CONCLUSION: This study shows that in Somalia, EC is the most common cancer in both genders. These high rates in Somalia suggest that environmental factors and dietary habits may have an effect. To reduce the incidence of EC and prevent its development, the population of Somalia should be educated and effective planning should be undertaken.